Study protocol: a randomized, double-blind, parallel, two-arm, placebo control trial investigating the feasibility and safety of immunoglobulin treatment in COPD patients for prevention of frequent recurrent exacerbations - Cowan, Juthaporn (Pilot Feasibility Stud, 2018)
BACKGROUND: Chronic obstructive pulmonary disease (COPD) is a chronic progressive inflammatory disease of the airways, associated with frailty, disability, co-morbidity, and mortality. Individuals with COPD experience increased risk and rates of acute exacerbation as their lung disease worsens. Current treatments to prevent acute exacerbation of COPD (AECOPD) are only modestly effective. New therapies are needed to improve the quality of life and clinical outcomes for individuals living with COPD and especially for those prone to frequent recurrent AECOPD. Recent research has suggested an association of gammaglobulin or immunoglobulin G levels with AECOPD and a favorable effect of an immunoglobulin treatment on the frequency of recurrent AECOPD, healthcare provider visits, treatments, and hospitalizations. However, control trials are required to confirm this apparent association and therapeutic effect. This study aims to assess if intravenous immunoglobulin (IVIG) therapy is feasible, safe, tolerable, and potentially effective in reducing the frequency of recurrent AECOPD. METHODS/DESIGN: Adult COPD patients at The Ottawa Hospital (TOH) will be recruited to partake in a randomized double-blind, parallel, two-arm, placebo control trial. Eligible patients will be administered either IVIG or normal saline following 1:1 randomization and every 4 weeks for 1 year. The primary outcome of feasibility will be determined by recruitment, patient adherence, safety and tolerance, success of the follow-up procedures, and outcome measurement. The safety and tolerability will be assessed through adverse events, adherence, and study withdrawals. Efficacy trends will be investigated by assessing incidence rates of AECOPD, improvement in quality of life, and healthcare services use and cost. DISCUSSION: The study results will inform larger studies designed to confirm a clinically significant therapeutic effect in identifiable populations which would be a major advance in the care of COPD patients. TRIAL REGISTRATION NUMBER: ClinicalTrial.gov, NCT03018652 and NCT02690038. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s40814-018-0327-z) contains supplementary material, which is available to authorized users.